Lesson Learned from a Case Study Investigation to Identify an Affordable Alternative to Cloud-based Worksharing - Dastider, Swarnali Ghosh; Rosa, Louis (Innovations in Science and Technology Vol. 8, 2022)
For construction projects using Virtual Design and Construction (VDC) or Building Information Modeling(BIM), real-time collaboration of numerous digital models is critical for success. Real-time collaboration enables users to collaborate in a multidisciplinary team to co-author multiple smart digital models for increased efficiency. This can be accomplished in two ways: with a physical server (Local Area Network/LAN server) or a cloud-based server (Wide Area Network/WAN server). A360, C4R, Collaboration for Revit, and BIM360Design collaborate are examples of cloud-based servers. However, the aforementioned cloud services are quite expensive, making it difficult for academia and small businesses to perform real-time collaboration using BIM/VDC models. Therefore, this case study aimed to identify an affordable alternative to the existing cloud-based server as part of the Virtual Design and Construction (VDC) course offered by the Construction Science and Management Department (CSM). A famous and free cloud server (Google) has been used as a WAN server in this study to host four multidisciplinary collaborative VDC central models for five users scattered across five different geographic locations and time zones. The study produced positive results towards establishing a real-time collaborative workshare environment. Therefore, this study can significantly benefit academia and small business. Additionally, this research also showed that a course can be designed to simulate the digital work environment of a small AEC firm, thus providing vital work experience to the students.